PELAKSANAAN KEWAJIBAN PELAKU USAHA TERHADAP PENGGUNA JASA ANGKUTAN MOTOR AIR DI PENYEBERANGAN SUNGAI SEKURA KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - NIM. A1011211159, SITI HARTINI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Motorized boat transportation is a very important means of transport for the people of Sekura, Sambas Regency. However, unfortunately, this transportation is not equipped with safety equipment for both passengers and cargo. This condition is very risky for passengers because the potential for damage due to accidents is very high. This thesis aims to examine how the implementation of the carrier